The Representation Level Of Knowledge Of The Health Of Ear and Hearing In Students Of Faculty Of Medicine Universitas YARSI Batch 2019 and Its Review According To an Islamic Perspective - Tiara dewi Puspita; Hastuti Rahmi; Toto Heriyanto (Junior Medical Journal, 2022)
Ear is one of the most important organ sense and play a big role in everyday life. Ear also has a main function as a sense of hearing which is indispensable in facilitating communication between humans, the frequency of sound humans can hear is between 20-20,000 Hz. According to World Health Organization (WHO), there are approximately 360 million (5.3%) people in the world who have hearing loss with 328 million (91%) happen on adults (183 million men and 145 million women) and 32 million (9%) cases happen on children. Given the importance of ear function, extra attention on caring is needed for ear health and hearing. Cleaning the ears must be done in the right way so that there are no accidents that will end up with irritation of the inside part of the ear. Most people clean their ears using cotton buds which will result an injury to the ear. There are commands in Islam regarding the importance of keeping the ears clean and also taking care of hearing.